Spermiogenesis alterations in the absence of CTCF revealed by single cell RNA sequencing - Torres-Flores, Ulises; Díaz-Espinosa, Fernanda; López-Santaella, Tayde; Rebollar-Vega, Rosa; Vázquez-Jiménez, Aarón; Taylor, Ian J.; Ortiz-Hernández, Rosario; Echeverría, Olga M.; Vázquez-Nin, Gerardo H.; Gutierrez-Ruiz, María Concepción; De la Rosa-Velázquez, Inti Alberto; Resendis-Antonio, Osbaldo; et al. (Frontiers in Cell and Developmental Biology, 2023)
CTCF is an architectonic protein that organizes the genome inside the nucleus in almost all eukaryotic cells. There is evidence that CTCF plays a critical role during spermatogenesis as its depletion produces abnormal sperm and infertility. However, defects produced by its depletion throughout spermatogenesis have not been fully characterized. In this work, we performed single cell RNA sequencing in spermatogenic cells with and without CTCF. We uncovered defects in transcriptional programs that explain the severity of the damage in the produced sperm. In the early stages of spermatogenesis, transcriptional alterations are mild. As germ cells go through the specialization stage or spermiogenesis, transcriptional profiles become more altered. We found morphology defects in spermatids that support the alterations in their transcriptional profiles. Altogether, our study sheds light on the contribution of CTCF to the phenotype of male gametes and provides a fundamental description of its role at different stages of spermiogenesis.